Competition of research and creative works as a form of self-realization of students - Alfia V. Moskvina; Lyubov A. Kochemasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
At the present stage of development of science, there is a need to develop theoretical and methodological grounds for intensifying the competition of research and creative works as a form of self-realization of students, defining ways of multipurpose involvement of students in research activities taking into account social realities that actualize the disclosure of ways to optimize and creative possibilities of a student in the professional and cognitive development and transformation of the surrounding world (with the updated azovatelnyh guidelines (research component in training, education entities active involvement in research activity).The article from the perspective of modern pedagogical science actualizes the possibility of competition as a form of self-realization of research activities of students of educational institutions of higher education (undergraduate level) in a modern university; analyzed the concept of "competition", which is investigated in modern edu cational theory; analyzes the direction and effectiveness of the competition organized in the space of the university;modern approaches to the content and organization of research activities of students of a pedagogical university in the context of the humanistic potential of the creative heritage of the teacher-researcher V.A. Sukhomlinsky. The positions of the creative heritage of the pedagogical thought of V.A. Sukhomlinsky in relation to the modern reading of their students.The practical significance of the research problem is confirmed by the fact that the developed conclusions can be used by scientific and pedagogical workers of the multilevel education system in determining areas and mechanisms that optimize the process of scientific and educational activities of bachelors in accordance with the requirements of the GEF for the purposeful mastery of the competence of scientific research in the context of optimal implementation of scientific strategies for learning, mastering the basic competences of scientific research are treacherous activities.